Detection of Polycyclic Aromatic Hydrocarbons in Water Samples by Annular Platform-Supported Ionic Liquid-Based Headspace Liquid-Phase Microextraction. (27th September 2018) - Sun, Xiaojie; Tan, Jie; Ding, Haiyan; Tan, Xiaojie; Xing, Jun; Xing, Lihong; Zhai, Yuxiu; Li, Zhaoxin
Abstract : In this paper, a new method of annular platform-supported headspace liquid-phase microextraction (LPME) was designed using ionic liquid as an extraction solvent, wherein extraction stability and efficiency were improved by adding an annular platform inside the extraction bottle. The ionic liquid 1-silicyl-3-benzylimidazolehexafluorophosphate was first synthesized and proved to be an excellent extraction solvent. Coupled with liquid chromatography, the proposed method was employed to analysis of polycyclic aromatic hydrocarbons (PAHs) in water and optimized in aspects of extraction temperature, extraction solvent volume, extraction time, pH, stirring rate, and salt effect of solution. The results indicated that this method showed good linearity ( R 2  > 0.995) within 0.5  µ g·L −1 to 1000  µ g·L −1 for PAHs. The method was more suitable for extraction of volatile PAHs, with recoveries from 65.0% to 102% and quantification limits from 0.01 to 0.05  µ g·L −1 . It has been successfully applied for detection of PAHs in seawater samples.